The effects of the introduction of tax incentives on retirement saving - Juan Ayuso; Juan F. Jimeno; Ernesto Villanueva (SERIEs - Journal of the Spanish Economic Association, 2019)
We examine the incidence on household consumption of the introduction of tax incentives to retirement saving. First, using data from a panel of tax returns we document that most contributions to pension funds are by older/high-income individuals. Then we use panel data from a consumption survey spanning the period 1985 and 1991 to find that there is substantial heterogeneity in the response of household saving to tax incentives. While the overall amount of new saving we estimate is limited (at most 19 cents per euro contributed on average), saving responses differ substantially across age groups: among the group of households between 56 and 65 years of age, the group that most actively contributed to the plan, there are very small consumption changes; among the group of households between 46 and 55 years of age, the decrease in (mostly durable) consumption expenditures is much larger.
Keywords: D14; H24; H55; 330; Pension funds; Tax incentives; Saving